THE IMPACT OF DECENTRALIZATION IN THE REGIONAL AUTONOMY ON HUMAN DEVELOPMENT IN INDONESIA - raharja, Wildan Taufik (JPAP: Jurnal Penelitian Administrasi Publik, 2020)
This study describes the concept of decentralization that addresses changes in operational tasks and delegation of authority in decision making from the central government to local governments. In other words, decentralization also considers as an instrument in the context of community empowerment related to human development nationally. Related to the implementation of the concept of decentralization in the era of regional autonomy, decentralization was designed to create new corruption in regional government. The majority of corruption was issued from the regional government in the last round. This study will answer the question of how the decentralization policy towards human development in Indonesia. This study uses secondary data analysis and literature review. Secondary data was obtained from the Central Statistics Agency which was then processed and reviewed based on the perspective of the researcher. Based on the results of the research that was thought about the implementation of the concept of decentralization in Indonesia, it was necessary to conduct a review related to supervision in the regions. The human development sustainability program in the area is determined by the commitment of the leader in carrying out his duties and role in running the government.